2018
DOI: 10.18203/2394-6040.ijcmph20181237
|View full text |Cite
|
Sign up to set email alerts
|

Perception of medical students towards serving rural people: A study from central India

Abstract: Background: India is facing critical problem of paucity of certified physicians in rural areas, although majority of the population resides in rural areas. According to rural health statistics report 2015, there is a deficit of 659 doctors in rural areas. The study was done with the objective to capture the perception among medical students (interns / postgraduates) about their preference of work place after graduation/post-graduation and to know the factors responsible for preference / non-preference.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
3
1
1
Order By: Relevance
“…In the present study, 78.9% students belonging to rural areas showed interest to join rural health services compared to 57.8% belonging to urban area. This finding is similar to findings by Bartwal et al, 4 Choudhary et al 5 and Saini et al 6 which showed that rural background students were more likely to practice in rural areas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, 78.9% students belonging to rural areas showed interest to join rural health services compared to 57.8% belonging to urban area. This finding is similar to findings by Bartwal et al, 4 Choudhary et al 5 and Saini et al 6 which showed that rural background students were more likely to practice in rural areas.…”
Section: Discussionsupporting
confidence: 91%
“…More females (68%) were inclined to work in rural areas as compared to males (57.6%) in the present study while Bartwal et al 4 and Choudhary et al 5 reported opposite findings in their respective studies.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Important hurdles included a lack of confidence or experience and the non-availability of senior/experienced doctors' support in the management of patients. Similar findings were also enumerated in a study conducted by Choudhary et al [ 12 ]. A study by Singh conducted in India revealed that undergraduate medical students preferred to do postgraduate courses because they felt that they could not manage patients with the inadequate knowledge they acquired as undergraduates [ 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…Factors expressed by students which promotes them to work in Rural health service of Uttarakhand were job security (68.5%), willingness to contribute to better health of the state (90.5%), good exposure for general practice (57.5%), building confidence as clinician (67.4%). Similar finding were elicited by studies done by Saini NK 10 , Chudhary Y 12 and Ossai E 13 . In current study, 83.3% expressed that duration of posting to rural health services should be reduced to 2 years which was also seen in Ugandan study.…”
Section: Discussionsupporting
confidence: 90%